prove it plse prove it...
Attachments:
![](https://hi-static.z-dn.net/files/d4a/49e4e500697f6afad05339fe8d41ce9b.jpg)
Answers
Answered by
8
Hiii....friend,
The answer is here,
Given that,
![= > \: \frac{a + ib}{c + id} = p + iq = > \: \frac{a + ib}{c + id} = p + iq](https://tex.z-dn.net/?f=+%3D+%26gt%3B+%5C%3A+%5Cfrac%7Ba+%2B+ib%7D%7Bc+%2B+id%7D+%3D+p+%2B+iq)
We can replace the " i " as " -i ".
![= > \frac{a - ib}{c - id} = p - iq = > \frac{a - ib}{c - id} = p - iq](https://tex.z-dn.net/?f=+%3D+%26gt%3B+%5Cfrac%7Ba+-+ib%7D%7Bc+-+id%7D+%3D+p+-+iq)
:-)Hope it helps u.
The answer is here,
Given that,
We can replace the " i " as " -i ".
:-)Hope it helps u.
Answered by
0
Answer:
Step-by-step explanation:
The answer is here,
Given that,
= > \: \frac{a + ib}{c + id} = p + iq
We can replace the " i " as " -i ".
= > \frac{a - ib}{c - id} = p - iq
Similar questions
Computer Science,
8 months ago
Science,
8 months ago
History,
8 months ago
Biology,
1 year ago
Math,
1 year ago